Pulmonary valve neo-reconstruction using the Ozaki technique in an adapted Ross procedure: case report - Kolesár, Adrián; Lukačín, Štefan; Rohn, Vilém; Benedík, Jaroslav; Toporcer, Tomáš (European heart journal. Case reports, 2025)
BACKGROUND: Aortic valve damage is the most common valvular heart disease in developed countries. The Ross procedure is an alternative to the aortic valve replacement with a prosthesis, providing a longer survival without reoperation and without the need for anticoagulation therapy. The unavailability of homografts for the pulmonary valve replacement is one of the limiting factors for a more common utilization of this therapeutic method. CASE SUMMARY: This case report presents a 35-year-old Caucasian male with a bicuspid aortic valve and severe aortic regurgitation. The patient underwent the Ross procedure with the stabilization of the aortic ring and sinotubular junction. A tubular prosthesis was created from the bovine pericardium, into which three neo-cusp valves were fashioned from autologous pericardium. The new pulmonary conduit was sutured distally to the distal pulmonary trunk and proximally to the right ventricular outflow tract. Four months post-operatively, the follow-up echocardiographic examination documented that the valve in the aortic position had no regurgitation, a maximum velocity of 1.25 m/s, and a peak gradient of 6.25 mmHg. The valve in the pulmonary position showed a trace regurgitation and mean pressure gradient of 13 mmHg. DISCUSSION: The combination of the modified Ross procedure with neo-cuspidalization according to Ozaki for a new pulmonary valve thus offers hope for an extended survival without reoperation in paediatric and non-elderly adult patients with an aortic valve dysfunction. This technique is additionally applicable by cardiac surgery centres without access to pulmonary homografts.
Keywords: Case report; Ozaki procedure; Aortic valve stenosis and regurgitation; Ross procedure